MOTIVASI MENUNAIKAN IBADAH HAJI DAN UMRAH - Bakri, Nazar (Universitas Islam Negeri Imam Bonjol Padang, 2004)
Pilgrimage (haji) is the fifth foundation of Islam, after saying two creed kalimah, confessing there is no God but Allah, that Muhammad is messenger (rasul) of Allah, praying (shalat), and pay for religious obligatory (zakat). There are many secret phylosophies (hikmah) of pilgrimate. The writer explains the secret phylosophy of the sacred pilgrimage.